Wavelength division multiplexed passive optical networks with colorless light sources - Xu, Zhao Wen (2010)
The emerging internet services need the future passive optical networks (PONs) to provide considerably increased capacity for subscribers. Wavelength division multiplexed (WDM) PON is expected to be the ultimate solution since dedicated wavelengths are assigned to each end user. The main objectives of this thesis are to investigate and propose novel low-cost colorless light sources and novel architectures for WDM-PONs supporting high data rates.